37 RE-AUDIT OF VITAMIN D SUPPLEMENTATION IN FRAIL OLDER ADULTS PRESENTING TO AN IRISH LEVEL 5 EMERGENCY DEPARTMENT. (25th October 2022) - Pender, C; O'Caheny, C; Byrne, C; Magner, S; Carey, S; Carrabine, N; Mitchell, M; Laguna, R; Harrington, G; Buckley, B; Smyth, H
Abstract: Background: The Department of Health published new guidance in November 2020 "Vitamin D advice for people aged 65 and older" which recommended that all adults ≥65 years should be supplemented with 15micrograms of Vitamin D daily. 55.5% of adults ≥65 years have insufficient/deficient vitamin D levels in winter (TILDA 2020). The Frailty Intervention Team (FIT) assess frail adults ≥65 years in the Emergency Department using medication review and Comprehensive Geriatric Assessment to identify vitamin D supplementation. The audit aim was to determine if compliance with the new guideline improved since the initial audit in January 2021. Methods: All patients who had a medicine reconciliation completed by the FIT Pharmacist in January 2022 were included in a retrospective audit. Patients were identified from the pharmacist's worklist. Data was collected from a Hospital Clinical System using a Microsoft Excel®. The data recorded included: Age, Sex, Rockwood Clinical Frailty Score (CFS) and vitamin D supplementation. Results: The FIT Pharmacist completed 66 medicine reconciliations in January 2022. The mean age (+/-SD) was 82.4 (+/-7.6) years. The male to female ratio was 1:1.75 The median CFS was 5 (mildly/moderately frail) with an IQR of 1. 68% (n=45) were prescribed vitamin D. Of those 89% (n=40) were prescribed a supplement containing at least 15micrograms of vitamin D. 32% (n=21) were not prescribed any vitamin D supplementation. 8% (n=5) were prescribed doses lower than 15micrograms of vitamin D. Conclusion: Compliance with the new guideline was 61% (n=40) in comparison to 65% (n=39) in the initial audit. The results are reflective of adherence to the new guideline in the community. The policy update and education provided post the initial audit has possibly influenced the prescribing of vitamin D in the acute setting which unless patients are re-presenting will not have been captured in the outcome of this re-audit.